THE COMMUNICATIVE LANGUAGE TEACHING TECHNIQUE TO MASTER SPEAKING SKILL FOR THE STUDENTS AT SMA NEGERI 3 PALEMBANG - Retika Wista Anggraini (Universitas Indo Global Mandiri, 2014)
Speaking is classified as a productive skill which takes an important role in mastering English. As productive skill, speaking becomes a measurement whether learners have mastered English or not. In this case, learners will think whether they have mastered the language or not by measuring their spoken ability in using the language itself. In addition, speaking is considered as a crucial part of second language teaching and learning because English learners need to master it in order to be able to communicate in real life. Communicative Language Teaching is the innovation of the foreign language teaching. Not only does it improve students’ communicative competence effectively, but also carries out the quality education in foreign language teaching. Furthermore, this paper is intended to discuss problems in testing oral proficiency, some elicitation techniques in testing oral proficiency and students’ low competence in using English for communication. Consequently, CLT is promoted students have many abilities to speak and understand English. The CLT technique to master speaking skill for the students at SMA Negeri 3 Palembang. It tries to improve speaking skill and make the students more active in the class because it contains some activities that encourage the students to speak up in the class.